Notch-EGFR/HER2 Bidirectional Crosstalk in Breast Cancer - Baker, Andrew T.; Zlobin, Andrei; Osipo, Clodia (Frontiers in Oncology, 2014)
The Notch pathway is a well-established mediator of cell-cell communication that plays a critical role in stem cell survival, self-renewal, cell fate decisions, tumorigenesis, invasion, metastasis, and drug resistance in a variety of cancers. An interesting form of crosstalk exists between the Notch receptor and the Epidermal Growth Factor Receptor Tyrosine Kinase family which consists of HER-1, -2, -3, and -4. Overexpression of HER and/or Notch occurs in several human cancers including brain, lung, breast, ovary, and skin making them potent oncogenes capable of advancing malignant disease. Continued assessment of interplay between these two critical signaling networks uncovers new insight into mechanisms used by HER-driven cancer cells to exploit Notch as a compensatory pathway. The compensatory Notch pathway maintains HER-induced downstream signals transmitted to pathways such as Mitogen Activated Protein Kinase (MAPK) and Phosphatidylinositol 3-Kinase (PI3K), thereby allowing cancer cells to survive molecular targeted therapies, undergo EMT, and increase cellular invasion. Uncovering the critical crosstalk between the HER and Notch pathways can lead to improved screening for the expression of these oncogenes enabling patients to optimize their personal treatment options and predict potential treatment resistance. This review will focus on the current state of crosstalk between the HER and Notch receptors and the effectiveness of current therapies targeting HER-driven cancers.